Multiple molecular dynamics time-scales in Hybrid Monte Carlo fermion simulations - PEARDON, MICHAEL JAMES; SEXTON, JAMES CHRISTOPHER (Elsevier, 2003)
A scheme for separating the high- and low-frequency molecular dynamics modes in Hybrid Monte Carlo (HMC) simulations of gauge theories with dynamical fermions is presented. The algorithm is tested in the Schwinger model with Wilson fermions.
PUBLISHED
Keywords: Pure & Applied Mathematics